Attractive landscapes and the residential dispersion of high income groups: a new elite of experiential consumers? Case study of Gran La Serena and Gran Concepción, Chile, 1965-2012 - Napadensky Pastene, Aaron (Universidad Diego Portales, 2019)
Historically, emerging elites have sought to reside in traditional and well-known high-income areas, as part of the construction of identity and the expression of their social status. Nowadays, new residential settlements, outside the established areas of high income, are expressing the predilection of elites for attractive landscapes and the search of beneficial experiences, rather than a prestige function; symptom -according to this study- of a renewed sensitive and playful conception of the territory. Two case studies have been analyzed: Gran La Serena and Grand Concepción, both of Chile. Through cartographies based on census data and other sources, the localization patterns of high socioeconomic groups and their relationship with the landscape attractiveness of the territory are evaluated. The results show, in both cases, remarkable parallelism between variables.